(untitled) (Journal of Chemical Engineering, 2014)
Chemical washing of fresh-assembled denim garment is a fundamental finishing process in textile and ready-made garment industries and has the largest effect on the physico-mechanical properties on finished denim garment. In this study, modification of denim trousers by washing using pumice stone mixed with bleaching powder was investigated. The fresh-assembled denim trousers, twill 3/1 weave and composition 100% cotton, have been processed by stone-bleach treatment using parameters namely concentration of bleaching powder (5.0 to 15.0 g/L) (owl) with 30% pumice stone (owg) at washing temperature 40oC and at pH 10.5 for treatment time 20 min in the fiber to liquor ratio of 1:10 in an industrial sample washing machine. In order to evaluate the influence of these washing parameters on the properties of denim trouser like tensile strength, fabric weight, color change, stiffness and water absorption, has been determined. Fabric surface was also examined by scanning electron microscope (SEM) and fluorescence microscope (FM). It can be concluded that the washing parameters had influenced on the physico-mechanical properties of finished denim garment. Especially stone-bleach treatment helped to get the specific color fading effect and softness of denim garment, which gave a new-look appearance and good wear performance to the fabric distinctly. The results indicate that for producing durable and sustainable denim garment the optimized washing condition for the best value is 10.0 g/L bleaching powder mixed with 30% pumice stone in the stone-bleach treatment. DOI: http://dx.doi.org/10.3329/jce.v28i1.18109 Journal of Chemical Engineering, Vol. 28, No. 1, December 2013: 36-40